Two Tolosa-Hunt Syndrome Accompanied By Peripheral Fasial Nerve Paralysis - Akçalı, Aylin; Yiğiter, Remzi; Mete, Ahmet; Yılmaz, Mustafa; Neyal, Münife (European Journal of Therapeutics, 2010)
Tolosa-Hunt syndrome is characterized of a painful ophthalmoplegia and is usually markedly responsive to corticosteroid therapy. In 2004 the re-defined diagnostic criteria of Tolosa-Hunt syndrome by International Headache Society the imaging findings have very important place. Cranial imaging demonstrates the contrast enhancement of cavernous sinus and orbital apex related to inflammation. We represented two case reports of Tolosa-Hunt syndrome. The cranial nerve involvement of 3., 4., 6., and first and the second branches of 5. were observed in both cases. One week later left peripheral facial nerve paralysis is added to the clinic in one of the cases. After excluding other diagnosis IV pulse steroid therapy is given and had fine response.